Peran Kunjungan Wisata Religi dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat Kota Palembang - Deta Septea; M. Habbi Husnul Mubarok; Sri Rahayu Wulaningsih; Yansuri , Yansuri; M. Daffa Firdianza (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Religious tourism in Palembang continues to grow through visits to historic mosques, sacred sites, and cultural heritage areas. These visits encourage local economic activities and create new livelihood opportunities for surrounding communities. This study assesses the role of religious tourism in improving the economic welfare of local residents. A descriptive quantitative approach was used. Data were collected through questionnaires, interviews, and field observations involving 49 respondents consisting of traders, service providers, and local managers. The findings show that higher levels of tourist visits increase business opportunities and household income. Areas with frequent tourist activity experience stronger economic dynamics, supported by the growth of trading activities and service-based enterprises. Residents who have lived longer in the area show a stronger ability to adapt and benefit from emerging economic opportunities. Religious tourism generates positive economic impacts through income growth, expanded employment opportunities, and strengthened micro and small enterprises. Overall, religious tourism serves as a key driver of local economic development and supports community-based economic empowerment in Palembang City.